An ulcerated exophytic tumour over the gluteal area- eccrine porocarcinoma in an immunocompetent female - Kumar, Ashok; Jagannath, Spandana; Phulware, Ravi H.; Mendiratta, Vibhu (International Surgery Journal, 2021)
Porocarcinoma is a very rare type of skin cancer arising from the eccrine sweat glands and is poorly understood. The exact pathogenesis is unknown. Clinical features are non-specific. It may present as a painless, slow growing mass or nodule, ulcer, plaque, swelling, wart, papule or naevus that increases in size over years to decades and may ulcerate or bleed upon trauma. They occur equally in both sexes and are most commonly found in the lower extremity. Though metastasis is rare, they are considered aggressive with high mortality rate. Diagnosis requires standard histopathological studies. Immunohistochemistry is useful in difficult cases. Treated early, eccrine porocarcinoma is curable by wide excision. The author reports the case of an eccrine porocarcinoma in the lower extremity of an elderly lady and a summary of its clinical, radiological and histological findings is illustrated.